REDUCTION OF FERRONICKEL SLAG USING COAL AND FERROSILICON AS REDUCING AGENT IN VACUUM CONDITION TO PRODUCE MAGNESIUM AND FERROALLOY - Levina, Gina
The ferronickel production process using the Rotary Kiln - Electric Furnace (RKEF) technology to process saprolite nickel ore has grown rapidly as well as being the main technology in the ferronickel production process. However, RKEF technology has several disadvantages including high consumption of electrical energy and the production of large quantities of solid waste or slag. 14 tons of slag are generated in the production of 1 ton ferronickel. The amount of slag produced will certainly increase along with the increasing demand for ferronickel metal. Primary and secondary smelting slag products are categorized as hazardous and toxic materials by the Government of Indonesia in Government Regulation of the Republic of Indonesia Number 101 of 2014. For now, slag is used only as a material in mining reclamation activities, as a mixture of construction materials, and as a road and beach backfill material. Ferronickel smelting slag has content of silica (SiO2) around 45%, magnesia (MgO) about 35%, and iron oxide (FeOx) about 10%. There is a potential to utilize ferronickel smelting slag as a raw material for producing Mg, Si, Fe or other metal alloys. The experiments were carried out by varying the reductant which is coal and ferrosilicon, and varying the addition of CaO flux starting from 0%, 5%, 10%, 15%, 20%, 25% to 30%. The experiments of the addition of CaO flux were carried out using a coal reducing agent according to the stoichiometric requirements to reduce ferronickel smelting slag samples. This ferronickel smelting slag reduction experiments were carried out in a vacuum furnace operating at a pressure of 10-1 Pa. The temperature of the vacuum furnace is increased by a heating rate of 10 oC per minute until the temperature reaches 1650 oC. After holding for 2 hours at 1650 oC, the temperature of the vacuum furnace was cooled by a cooling rate of 10 oC per minute to room temperature. Metal particles and slag that are produced were then observed using Optical Microscope (OM) and analyzed by Scanning Electron Microscope - Energy Dispersive X-Ray Spectroscopy (SEM-EDS). Observations with OM were carried out to determine the microstructure of the produced metal and slag. The SEM- EDS analysis was carried out to determine the microstructure in more detail and to determine the levels and distribution of elements in the produced metal and slag. The experimental results obtained in this study are the weight loss of the samples, microstructure analysis using an optical microscope, chemical composition of the phases in the sample from spot analysis using SEM-EDS, and the average chemical composition of the sample using SEM- EDS. Coal reducing agents shows a higher percentage of sample weight loss compared to the use of ferrosilicon reducing agents. The reduction experiment of ferronickel smelting slag using a coal reducing agent showed a sample weight loss of 56.45% without added flux and 50.17% with the use of 30% added CaO flux, whereas using a ferrosilicon reducing agent showed a sample weight loss of 27.98% without added flux and 27.89% with the use of 30% CaO flux. The use of a coal reducing agent can reduce more iron oxide in the slag sample from smelting ferronickel into ferrous metal than the use of a ferosilicon reducing agent. The reduction results of the ferronickel smelting slag without the use of flux has Fe, Si, and Cr content of 72.4%; 17.3%; and 8.7% for the use of coal reducing agents, and in the amount of (spot 1 and 2) 23% and 6.6%; 73.8% and 90.1%; 1.8% and 1.09% for the use of ferrosilicon reducing agents. The reduction results of ferronickel smelting slag using added CaO flux 30% contained Fe, Si and Cr content of 85.1%; 4.4%; and 5.3% for the use of coal reducing agents, and (spot 1 and 2) 40% and 61%; 37.6% and 56.8%; 0.98% and 1.23% for the use of ferrosilicon reducing agents. The addition of 30% CaO added flux causes a decrease in magnesium content in the slag by 10% using either coal or ferrosilicon reducing agents.